2011
DOI: 10.1021/la203753q
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Two Kinds of Fluorinated Hydrogenated Micelles as Building Blocks for the Design of Bimodal Mesoporous Silica with Two Ordered Mesopore Networks

Abstract: A simple and effective route has been developed for the synthesis of bimodal (3.6 and 9.4 nm) mesoporous silica materials that have two ordered interconnected pore networks.Mesostructures have been prepared through the self assembly mechanism by using a mixture of polyoxyethylene fluoroalkyl ether and triblock copolymer as building block. The investigation of the R F 8 (EO) 9 /P123/water phase diagram evidences that in the considered surfactant range of concentrations, the system is micellar (L 1 ). DLS measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…For example, ah ierarchical combination of pores allows the reduction of transport limitations in catalysis, resultingi nh ighera ctivities and better control over selectivity. [11] Nonetheless, one main challenge is to produce direct proof of the synergetic formation of the two mesoporous networks and that the final material is not just two unconnected networks. [7] However,h ierarchical porous materials with two sets of mesopores have been less investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, ah ierarchical combination of pores allows the reduction of transport limitations in catalysis, resultingi nh ighera ctivities and better control over selectivity. [11] Nonetheless, one main challenge is to produce direct proof of the synergetic formation of the two mesoporous networks and that the final material is not just two unconnected networks. [7] However,h ierarchical porous materials with two sets of mesopores have been less investigated.…”
Section: Introductionmentioning
confidence: 99%
“…mesoporouss ilica materials through ao ne-step synthesis process. [11] Nonetheless, one main challenge is to produce direct proof of the synergetic formation of the two mesoporous networks and that the final material is not just two unconnected networks. In situ small-angle X-ray scattering (SAXS) kinetic studies are ap owerful technique for such investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, they are of particular interest for catalysis, for sorption and for the engineering of pore systems [40,41]. Many studies are focused on the synthesis of meso-macro, micro-macro or micro-mesoporous materials [42][43][44][45][46][47][48], but only a few of them deal with systems in which bimodal mesopore structures are present [20][21][22][23][24]. In addition, the recovered materials adopt either disordered bimodal mesopore arrangements or ordered mono-modal mesopore with small size template molecular systems embedded in larger entities [49].…”
Section: Resultsmentioning
confidence: 99%
“…and fluorinated compounds, either mixed micelles containing both surfactants in a well-defined proportion, or two kinds of micelles enriched in one of the two components can be formed [4,[12][13][14][15][16][17][18]. In regards to the synthesis of mesoporous materials, we can thus take benefit of these systems to design bimodal mesostructures on the condition that the two surfactants have hydrophobic chains with different sizes [19][20][21][22][23][24]. For example Antionetti et al have reported the synthesis from mixed micellar solutions of immiscible fluorinated and hydrogenated surfactants of mesoporous silica monoliths with bimodal pore size distribution via the nanocasting process [20].…”
Section: Introductionmentioning
confidence: 99%
“…On the condition that the two templates have hydrophobic chains with different sizes, mixtures of hydrogenated and fluorinated surfactants are excellent candidates to design these dual-mesoporous silica materials via a one-step synthesis process. In a previous letter [36] , taking advantage of the behavior of mixed hydrogenated/fluorinated systems, we have demonstrated that dual-mesoporous materials can be obtained from a mixture of the polyoxyethylene fluoroalkyl ether R F 8 (EO) 9 and the Pluronic (P123). It should be noted that syntheses have been performed only under the experimental conditions that give well ordered mesostructures using the pure fluorinated surfactant.…”
Section: Introductionmentioning
confidence: 99%